Integration of Stock Markets between Indonesia and Its Major Trading Partners - Karim, Bakri Abdul; Majid, M. Shabri Abdul; Abdul Karim, Samsul Ariffin (Gadjah Mada International Journal of Business, 2009)
Using Autoregressive Distributed Lag (ARDL) and Vector Autoregressive (VAR) frameworks, this study examines the integration between the emerging stock market of Indonesia and its major trading partners (i.e., Japan, the U.S., Singapore, and China). During the period of July 1998 to December 2007, the Indonesian stock market is found to be integrated with its major trading partners. Thus, this implies that there is a limited room available for investors to gain risk-reduction benefits through diversifying their portfolio in those markets. Meanwhile, in the short run, the Indonesian market responds more to shocks in the U.S. and Singapore than in Japan and China. In designing policies pertaining to its stock market, the Indonesian government should take into account any development in the stock markets of its major trading partners, particularly the U.S. and Singaporean markets.